A new genus and three new species of jumping spiders (Araneae: Salticidae) from Sri Lanka - Kanesharatnam, Nilani; Benjamin, Suresh P. (European Journal of Taxonomy, 2018)
A new genus of jumping spiders, Bavirectagen. nov. is proposed to include the type species B. flavopuncta gen. et sp. nov. and Bavirecta exilis (Cao et al., 2016) gen. et comb. nov. Distinguishing characters of Bavirecta gen. nov. include: 1) tubular abdomen, 2) enlarged front legs, 3) straight and pointed embolus, broadest proximal lobe with black blotches, 4) prolateral tegular lobe, 5) widely separated anterior atria. Furthermore, two new species, Schenkelia aurantia sp. nov. (♂♀) and Brancus calebi (♂) sp. nov., are described and diagnosed. Mogrus frontosus (Simon, 1871) is redescribed based on a male collected from Mandaitivu Island of Jaffna District in Sri Lanka. The genera Brancus Simon, 1902, Mogrus Simon, 1882 and Schenkelia Lessert, 1927 are reported for the first time from Sri Lanka (Brancus and Schenkelia are recorded for the first time outside Africa).